Effects of Mirror Therapy for Improving the Motor Function of Upper and Lower Extremities in Patients with Stroke – A Quasi Experimental Study - Qurba Kiran, Zubair Ahmad, Abdul Rab, Momin Mukhtar, Atif Malik, Mahanoor Shafiq, Sana Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Stroke is defined as the rapid onset of focused or generalized disturbance of cerebral functions that lasts more than 24 hours. Speech issues and weakness on one side of the body are typical stroke signs and symptoms. Patients with upper limb disability following a stroke were unable to carry out particular gripping and manipulating tasks. Objective: Determine Effects of Mirror Therapy for Improving the Motor Function of Upper and Lower Extremities in Patients with Stroke Material and Methods: A quasi-experimental study was carried out in which the subjects in between 45-60 years, ischemic and hemorrhagic stroke male and female were recruited. Subjects were divided into two groups. In Group A tasks given, were performed by patients in front of mirror and with the unaffected limb. The mirror therapy was given 5 days a week with 50 min session and Electrical stimulation for 10 minutes. In Group B the patients were given PNF techniques for 6 weeks. The outcome tool used for evaluation of upper and lower limb assessment was Modified Fugl Meyer functional tool. The data was analyzed using SPSS. Results: The pretest and posttest observations for motor assessment of upper, within the mean score of Group A in pre assessment was 31.47±9.67 mid assessment was 34.73±10.47 and post assessment was 238.53±10.72 (0.001) showing significant improvement with intervention of Group A. Motor assessment score in Group B in pre assessment was 36.07±11.25 mid assessment was 43.27±9.83 and post assessment was 49.47±9.48 (0.001) showing significant improvement with intervention of Group A. Motor assessment score in Group B in pre assessment was 15.27±4.56 mid assessment was 21.73±5.23 and post assessment was 28.47±4.56 (0.001) showing significant improvement with intervention of Group A at P value <.05 showing effectiveness of both techniques. Practical Implication: This study will also help peer group in practicing and rehabilitating the stroke patients with new techniques. There is a need to incorporate easy, simple, economic, patient directed and effective treatment techniques to enhance recovery following stroke. There is less data available on comparison between conventional physical therapy and mirror therapy in the up-per limb in the past. Conclusion: We have concluded that both the PNF and MT were effective in improving score motor function but MT were found to have better effect as compared to PNF . Patient can gain muscle control, coordination and know the limitation of movement. It ultimately reduces the muscle atrophy and disability. Keywords: Mirror therapy, Motor function, Patient, Lower Extremity.